Strategic Digital Branding on TikTok: A SOSTAC-Based Case Study of Camille Beauty’s Skincare Marketing in Indonesia - Yuliono, Dharanisya Dzakirah; Rochmaniah, Ainur (Universitas Ahmad Dahlan, 2025)
TikTok has emerged as a powerful platform for marketing communication, particularly for beauty and skincare brands targeting digitally native consumers. This study investigates the TikTok-based digital marketing strategy of Camille Beauty, an Indonesian skincare brand, through the lens of the SOSTAC framework, comprising Situation Analysis, Objectives, Strategy, Tactics, Action, and Control. Employing a qualitative descriptive approach, the research integrates content observation of the brand's TikTok account (@camillebeauty_official) with in-depth interviews involving consumers and content-engaged users. The findings reveal that Camille Beauty effectively leverages TikTok’s platform affordances—such as short-form videos, live streaming, influencer collaborations, and user-generated content—to build brand visibility, consumer trust, and product sales. The brand's content strategy includes educational posts, product demonstrations, testimonial videos, and promotional campaigns, which are designed to align with audience preferences, especially among Gen Z women. The SWOT and 5S (Sell, Serve, Speak, Save, Sizzle) analyses further illuminate the brand’s strengths, challenges, and marketing goals. Data triangulation indicates that Camille Beauty's consistency in content creation and real-time interaction significantly contributed to follower growth and increased customer conversion. This study contributes to the expanding literature on social media marketing by offering a contextualized case of how TikTok content influences consumer engagement in the beauty sector. The findings highlight the importance of data-driven control mechanisms, platform-specific tactics, and strategic positioning in a competitive digital environment. The research provides actionable insights for marketers aiming to optimize content strategies within short-video platforms.